FITRAH-BASED EDUCATION - Astuti, Mardiah (PD PGMI se Indonesia, 2017)
In the general concept of Islam, it is stated that primordial human nature (Fitrah in Arabic) is that human beings are born with an innate inclination of tawhid (Oneness). Existing creation and the natural structure has the fact that human beings are born with their natural belief of one God which is called tawhid religion. Islam, as a Fitrah religion, fits not only in men’s diversity but also supports their growth and development. This makes their existence completed with perfect personality. The concept of education on the basis of fitrah has two primary goals. Firstly, it is to trigger and encourage the development of good personality rooted from Fitrah of the students. The good personality has two main dimensions, which are social and personal dimension, which lead to self awareness. By having self awareness, students are expected to have fundamental potential which should be developed optimally. Secondly, it is to return back to th concept of Oneness so that the universe becomes a means of Zikr (devotional acts in Islam in which short phrases or prayers, glorifying Allah, are repeatedly recited silently within the mind or aloud) and learning sources for students. In line with the goals of the Fitrah concept in the islamic educational system, students’ Fitrah can be built correctly and perfectly as a moslem. A pious man who has great relationship with Allah SWT, other human beings, and nature positively and constructively is called Manusia yang beriman dan bertaqwa serta memiliki berbagai kemampuan aktualisasi hubungan dengan Allah swt, sesama manusia, dan alam secara positif konstruktif, inilah yang disebut transcedental humanism theocentric